2016
DOI: 10.4236/wjcs.2016.611021
|View full text |Cite
|
Sign up to set email alerts
|

“A Prospective Randomized Case-Control Study To Evaluate Mini Right Thoracotomy versus Conventional Sternotomy For Mitral Valve Repair In Rheumatic Heart Disease.”

Abstract: Purpose: Right mini thoracotomy has been evaluated in many studies for mitral valve repair mainly in degenerative valvular disease but not in rheumatic heart disease. Mitral valve repair is more challenging in rheumatic etiology due to complexity of lesions. This prospective randomized case control study was designed to evaluate repair through mini right thoracotomy and to compare the clinical and echocardiographic outcomes with sternotomy in rheumatic patients. Methods: 25 patients of rheumatic heart disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There is still a lack of evidence regarding the use of the minimally invasive techniques for RMS. Chahal et al [16] published one randomized case-control study comparing right-sided minithoracotomy with sternotomy in patients with rheumatic MV lesions, during which it was shown that the minithoracotomy group had shorter ventilation time, hospitalization, and time…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of evidence regarding the use of the minimally invasive techniques for RMS. Chahal et al [16] published one randomized case-control study comparing right-sided minithoracotomy with sternotomy in patients with rheumatic MV lesions, during which it was shown that the minithoracotomy group had shorter ventilation time, hospitalization, and time…”
Section: Discussionmentioning
confidence: 99%
“…effect, shorter period of hospitalization, and reduce trauma, while maintaining the safety and effectiveness compared with median sternotomy [Chernov 2020;Chahal 2016]. Anh et al reported on 142 patients with rheumatic mitral valve dysfunction who underwent MIMVS at the University Medical Center of Ho Chi Minh City in Vietnam.…”
Section: E182mentioning
confidence: 99%